Children's Positive and Negative Emotional Responses to an HIV Disclosure Study in South Africa - Ramsammy, Candice W.; Galvin, Lisa; Joyce, Celeste; Leshabane, Given; Buckley, Janice; Otwombe, Kennedy; Liberty, Afaaf; Violari, Avy (Frontiers in Pediatrics, 2022)
The benefits of HIV status disclosure to children is widely cited. However, few studies have reported how children respond to the process in a longitudinal fashion. This paper describes children's responses, as documented by healthcare providers (HCPs), during a longitudinal disclosure study conducted at Chris Hani Baragwanath Academic Hospital in Soweto, South Africa. Two HCPs facilitating disclosure recorded observations of 30 participating children (60% female), aged 7-13 years. Participants attended an average of six disclosure counseling sessions over 78 weeks. Observations documented by HCPs included the child's behavior and expressed emotions during the disclosure counseling sessions. The data was analyzed using content analysis. Mixed responses were observed in children who received full disclosure (27/30), with more children responding with strong negative emotions (16/27). However, 10 of those responded well to reassurance, and emotionally improved over subsequent sessions. Improvements were also observed in the communication and relationship between caregivers and children (17/30). Although most children understood the disclosure content (17/30), many were avoidant of the topic of HIV (16/30). With the understanding of the complex range of emotions elicited by HIV disclosure, we can better prepare HCPs on what to anticipate and train caregivers to further manage negative responses post-disclosure. This in turn may lead to more positive experiences of disclosure and the child's healthy acceptance of their HIV status.